1973
DOI: 10.1902/jop.1973.44.2.100
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Plaque in Humans By Two Experimental Oral Rinses

Abstract: THE ROLE OF DENTAL PLAQUE in the generation of cal-culus is now well recognized. Until recently, inhibition of crystallization of the plaque to hydroxyapatite was emphasized as the route to the prevention of calculus deposits. This approach is now giving way to attack on the microbial component of plaque. Löe, 1 for example, reported elimination of dental calculus in subjects appropriately treated with the antimicrobial agent chlorhexidine gluconate. Calculus reduction by the use of chemical agents whose princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Previous reports on the plaque-inhibiting effect of zinc citrate containing solutions have been contradic tory [Fischman et al, 1973;Addy et al, 1980]. In the present study, a solution of 12.0 m M Zn2+ from zinc citrate decreased plaque accumulations ( fig.…”
Section: Discussionsupporting
confidence: 51%
“…Previous reports on the plaque-inhibiting effect of zinc citrate containing solutions have been contradic tory [Fischman et al, 1973;Addy et al, 1980]. In the present study, a solution of 12.0 m M Zn2+ from zinc citrate decreased plaque accumulations ( fig.…”
Section: Discussionsupporting
confidence: 51%
“…In the present investigation, the favorable anticalculus effects observed are likely to be due to a combination of the antiplaque effect of the triclosan/zinc combination and the anticrystal formation properties of zinc citrate. Ritchie et al 33 have observed less calculus in dogs after applications of mouthrinses containing a zinc salt and quaternary ammonium compounds, and Fischman et al 34 have reported reduced calculus in humans after they had used mouthrinses containing zinc and an antimicrobial agent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the use of topically applied zinc salts for the con trol of plaque and/or calculus deposits in vivo [Addy et al, 1980;Fischman et al, 1973;Hanke, 1940;Picozzi et al, 1972;Schmid et al, 1974], Sources of zinc used in these and subsequent preparations have included zinc chloride [Lobene et al, 1985;Schmid et al, 1974], zinc citrate [PretaraSpanedda et al, 1985;Addy et al, 1980], combinations of zinc citrate and zinc tribromsalan [Fischman et al, 1973] and combinations of zinc chloride and sanguinarine [Southard et al, 1985]. Cur rently, a number of commercial dentifrice products are being marketed which con tain zinc citrate or zinc chloride for plaque and/or calculus control.1…”
mentioning
confidence: 99%